Pengaruh Penerapan Collaborative Learning Berbantu Ispring Presenter terhadap Hasil Belajar Program Linear - Venty Meilasari (Universitas Muhammadiyah Kotabumi, 2019)
This research was aimed to investigate the influence of implementation collaborative learning with ispring presenter toward linear programing outcomes. This research was quantitative research. This also used the pre-experimental design with one-group pretest-posttest design. The sample were all students of the 4th of mathematic departement of Universitas Muhammadiyah Kotabumi in academic year 2017/2018. The sample was taken using purposive sampling. The instruments used was linear programing outcomes test. The conclusions of this research was that there is positive influence of implementation collaborative learning with ispring presenter toward linear programing outcomes.